2013
DOI: 10.1152/ajpendo.00216.2012
|View full text |Cite
|
Sign up to set email alerts
|

Delayed development of specific thyroid hormone-regulated events in transthyretin null mice

Abstract: Thyroid hormones (THs) are vital for normal postnatal development. Extracellular TH distributor proteins create an intravascular reservoir of THs. Transthyretin (TTR) is a TH distributor protein in the circulatory system and is the only TH distributor protein synthesized in the central nervous system. We investigated the phenotype of TTR null mice during development. Total and free 3',5',3,5-tetraiodo-L-thyronine (T(4)) and free 3',3,5-triiodo-L-thyronine (T(3)) in plasma were significantly reduced in 14-day-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 64 publications
2
19
0
Order By: Relevance
“…In this study, shRNA that silenced TTR , was used to investigate (i) inhibition of myotube formation based on MYOG and MYL2 mRNA expression (ii) changes in mRNA expression of the calcium channel related genes, STIM1, Orai1, Cav1.1 and Cav3.1, and (iii) time dependent occurrence of voltage-gated calcium currents during myogenesis. Our results are in accordance with Mock et al [35], in which they demonstrate the decrease in muscle mass of a TTR null mouse.…”
Section: Discussionsupporting
confidence: 94%
“…In this study, shRNA that silenced TTR , was used to investigate (i) inhibition of myotube formation based on MYOG and MYL2 mRNA expression (ii) changes in mRNA expression of the calcium channel related genes, STIM1, Orai1, Cav1.1 and Cav3.1, and (iii) time dependent occurrence of voltage-gated calcium currents during myogenesis. Our results are in accordance with Mock et al [35], in which they demonstrate the decrease in muscle mass of a TTR null mouse.…”
Section: Discussionsupporting
confidence: 94%
“…Another likely candidate is transthyretin, whose synthesis in the brain is restricted to choroid plexus. The transthyretin gene is highly expressed throughout development in rat choroid plexus ([52] and data not shown), and this thyroxin carrier was shown to be important and necessary for various aspects of normal brain development [53]. …”
Section: Resultsmentioning
confidence: 99%
“…1113 Mice with both copies of the gene silenced display a behavioral abnormality throughout life, and it has been suggested that they exhibit a physical developmental delay that normalizes in young adults. 1416 …”
Section: The Ttr Gene and Proteinmentioning
confidence: 99%